Public Acceptance of Utilization of Water Reuse in Community-Based Sanitation Infrastructure (Case Study: Bandung City) - Fajar Lizmawan; Dyah Wulandari Putri; Sri Maryati (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
The difficulty of sustainable development is hampered by water scarcity and increased water demands, particularly in urban areas. Domestic wastewater discharges contaminate surface water bodies, such as the Citarum River. These difficulties, which disproportionately affect low-income populations, contribute to health consequences like diarrhoea and stunting. The Reinvented Toilet Project, a community-based sanitation programme, was put into place in Pasirluyu Village, Bandung, to combat water pollution. In order to lower water demand and sewage generation, it includes water reuse, reusing processed wastewater for other applications. This study assesses Pasirluyu Village infrastructure users' attitudes towards social water reuse. Surveys gathered data on demographics, views on water recycling, and information about sanitary facilities. Spearman correlation tests and descriptive analysis were carried out. The outcomes show that infrastructure users have a positive impression of water reuse. However, some people are hesitant to use reclaimed water for activities that require close personal touch. The relationship between public acceptability of water reuse for flushing toilets and acceptance for other purposes raises the possibility of a cascading expansion of water reuse practises. Keywords: community-based infrastructure, households, water reuse, water reuse aceptance